Characteristics and hazard risk of microplastics in Sinonovacula constricta: from farming to market - Chen, Bin (Frontiers in Marine Science, 2023)
In this paper, I selected Sinonovacula constricta, a typical representative of commercial bivalve shellfishes from Zhangzhou city, and found that microplastics were detected in all the samples with small size. The abundance in farm samples (3.65 n/g) was higher than in market (0.89 n/g), despite their smaller weight, which were mainly contributed by body fluid. Microplastics transported from the body fluid to the viscera and then metabolized into muscle were substantially reduced (69.3%), only 0 or 1 microplastics observed in the muscles on the micron scale. The microplastics detected in the market samples were mainly concentrated in the viscera, accounting for 81%, while distributed in all the organs of farm samples, with body fluids the most accounting for 52%. A total of four shapes were detected, with the highest percentage of fibrous shape, while foam-like microplastics were not detected in the market samples. The abundance was not correlated with sample weight, but market samples showed positive correlation. A total of seven polymers were detected, with the highest rate of PP (27%). The polymer risk level reached level III. The percentage of PVC in the market samples exceeded that of farms, which resulted in a higher hazard risk index despite their lower abundance. The cleaning process and excretory behavior, from farm to market seafood pond, greatly reduced microplastic contamination and the risk. This paper can provide some baseline for the study of microplastic characteristics of bivalve shellfish, and decision making on plastic management from aquaculture farm to market, especially for seafood security.